THE CHARACTERISTICS OF YAM (Dioscorea Alata) STARCH EDIBLE FILM - Ulyarti Ulyarti; E. Maryana; I. Rahmayani; Nazarudin Nazarudin; Susilawati Susilawati; Aris Doyan (Jurnal Penelitian Pendidikan IPA, 2019)
The purpose of this study was to determine the physical, mechanical and barrier properties of yam starch edible film. This research used Randomized Block Design (RAK).grouping the cultivar into 2, white and purple water yam. The starch concentration used were 1,33%, 2%, 2,67%, dan 3,33%.The results showed that the two cultivars produced similar properties of edible film.  The concentration of water yam starch affected transparency, thickness, water vapour transmision rate (WVTR) and compressive streght of edible film, but did not affect its solubility in water. The starch concentration of 2.67% was found to be the most appropriate concentration which produce edible film with thickness 0.12 to 0.13 mm, transparency 12.42 to 13.24%/mm, solubility 84.36 to 86.60%, water vapor transmission rate 1.16 x10-2 to 1.08 x10-2 g/sec/m2, and compressive strenght 48.10 to 49.35 N/m2Keywords:Edible Film, Water Yam, Cultivars, Starch concentration